Fever or temperature instability is a warning sign in neonates: A case of complicated meningitis. - Mohamed, Mossad Abdelhak Shaban; Abu Bakar, Asrar; Alsabie, Mohamed Nidal; Hammour, Ahmad; AlamRaza, Habib; Gadallah, Naser (2019)
Introduction: A complete septic profile including lumbar puncture (LP) ought to be done in febrile neonates unless other consideration. Presentation: A 25-day old baby girl presented with fever and decreased oral intake for three days. She has no significant prenatal, natal or postnatal history. At presentation, she appeared lethargic but had no abnormal findings other than fever of 38.4 degrees and congested throat. Her anterior fontanelle was normal, and her reflexes slightly brisk. Full blood count, CRP, serum electrolytes and urine are normal. The baby was admitted for intravenous fluids and penicillin. On the third day of admission, she developed generalised convulsion aborted by diazepam. A complete septic profile, including lumbar puncture, was performed and the patient was started on cefotaxime and acyclovir. The CSF results showed leucocytosis, mainly neutrophils and high protein. She continued to have fever of which CT Brain was done and revealed an abscess at the left temporal area. About 30 ml of pus was surgically drained and the patient completed 21 days of antibiotics. As a sequela, she became hemiplegic with both visual and hearing deficiencies and is currently under a multidisciplinary team follow up. Further investigations revealed no immunodeficiency and follow up MRI showed brain atrophy. Conclusion: Lumbar puncture is an essential pillar of septic profile for a febrile neonate. Often blood test including CRP and physical examination, would appear normal despite meningitis. Effective communication is highly required to convince the family for the essentiality of lumbar puncture in early diagnosis and timely management.